2022
DOI: 10.1002/admt.202200711
|View full text |Cite
|
Sign up to set email alerts
|

Metahouse: Noise‐Insulating Chamber Based on Periodic Structures

Abstract: Noise pollution remains a challenging problem requiring the development of novel systems for noise insulation. Extensive work in the field of acoustic metamaterials has led to various ventilated structures which, however, are usually demonstrated for rather narrow regions of the audible spectrum. In this work, the idea of metamaterial‐based systems is further extended, developing the concept of a metahouse chamber representing a ventilated structure for multiple band noise insulation. Broad stop‐bands originat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…To form a periodic structure the resonators are arranged in pairs as it allows to broaden bang-gaps due to the strong local coupling [41]. The studies of transmission properties are performed for the semi-infinite structures which in this work are understood as structures having finite thickness along the direction of the incident plane wave propagation and infinitely periodic along the other direction [Figure 1(b)].…”
Section: System Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…To form a periodic structure the resonators are arranged in pairs as it allows to broaden bang-gaps due to the strong local coupling [41]. The studies of transmission properties are performed for the semi-infinite structures which in this work are understood as structures having finite thickness along the direction of the incident plane wave propagation and infinitely periodic along the other direction [Figure 1(b)].…”
Section: System Descriptionmentioning
confidence: 99%
“…Unless it is stated otherwise, the thickness of the semiinfinite structure is 3 pairs of the resonators since in Ref. [41] it was demonstrated that such thickness is enough to experimentally observe pronounced stop-bands corresponding to the band-gaps of an equivalent infinite system [Figure 1(b)]. It might be argued that a structure with 3 unit cells can not be called a truly periodic one and variation of parameters in the direction of wave propagation is not enough to claim it to be chirped.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25] Recently, the application of metamaterials has been extended to reduce tire noise and a noise insulating chamber. [26,27] Among various metamaterial designs, space-coiling metamaterials have attracted significant attention for their ability to achieve low-frequency absorption with deep subwavelength thickness. [15,16,[22][23][24][25] The extraordinary absorption performance is attributed to various mechanisms, including local resonance, [14,15] negative and zero effective material properties, [20,21] critical coupling, [16] Fabry-Pérot, and quarterwavelength resonance.…”
Section: Introductionmentioning
confidence: 99%